Dexamethasone-loaded zeolitic imidazolate frameworks nanocomposite hydrogel with antibacterial and anti-inflammatory effects for periodontitis treatment. (December 2022) - Li, Ning; Xie, Lianyan; Wu, Yicheng; Wu, Yan; Liu, Yongjia; Gao, Yiming; Yang, Jie; Zhang, Xiuyin; Jiang, Liting
Abstract: Periodontitis is a bacterial-induced, chronic inflammatory disease characterized by progressive destruction of tooth-supporting structures. Pathogenic bacteria residing in deep periodontal pockets after traditional manual debridement can still lead to local inflammatory microenvironment, which remains a challenging problem and an urgent need for better therapeutic strategies. Here, we integrated the advantages of metal-organic frameworks (MOFs) and hydrogels to prepare an injectable nanocomposite hydrogel by incorporating dexamethasone-loaded zeolitic imidazolate frameworks-8 (DZIF) nanoparticles into the photocrosslinking matrix of methacrylic polyphosphoester (PPEMA) and methacrylic gelatin (GelMA). The injectable hydrogel could be easily injected into deep periodontal pockets, achieving high local concentrations without leading to antibiotic resistance. The nanocomposite hydrogel had high antibacterial activity and constructs with stable microenvironments maintain cell viability, proliferation, spreading, as well as osteogenesis, and down-regulated inflammatory genes expression in vitro . When evaluated on an experimental periodontitis rat model, micro-computed tomography and histological analyses showed that the nanocomposite hydrogel effectively reduced periodontal inflammation and attenuated inflammation-induced bone loss in a rat model of periodontitis. These findings suggest that the nanocomposite hydrogel might be a promising therapeutic candidate for treating periodontal disease. Graphical abstract: Image 1